Claim for Damages in Criminal Actions to Achieve Justice for Victims - Gatra Yudha Pramana (Ius Poenale, 2020)
Settlement of criminal cases, the criminal justice system pays more attention to the rights of the accused by law, while the victim's right to obtain justice in the form of compensation has not been maximally realized. This paper aims to see the implementation of the claim for compensation in criminal offenses. This study uses normative and empirical juridical methods. The results showed that the position of the victim in the Criminal Justice System, both according to the Criminal Code (KUHP) and the Criminal Procedure Code (KUHAP) are currently not equivalent to the perpetrators of criminal acts. So to file a claim for compensation, the victim of a criminal offense has not received legal certainty. Even though the Criminal Procedure Code and the Criminal Code have given a little room for victims to get true justice as a result of acts or criminal acts committed by criminals.